Os parklets na cidade de São Paulo - Calca, Paula Renata Felipe de Almeida (2019)
This dissertation seeks to make a reflection on the parklets in the city of São Paulo, elucidating the implementation of the same, their real need, as is their implementation process and guidelines and regulations defined by the city. Analyzes as well the limits and possibilities of occupation of public spaces in the city of São Paulo, the private and public appropriations of urban spaces. Inquires to what extent the streets are able to meet the needs of the population of the city, highlighting new actions to be applied, their consequences and innovation in the use of public space. In this context, we give special emphasis to the parklets, a contemporary strategy of converting private parking space into public leisure spaces. To emphasize when and where this strategy emerged, in the light of urban studies, more concretely, the reflection on urbanization, metropolization and urban conversion in the city of São Paulo. Regarding parklets, concepts, experiences, opinions and user interaction, the role of public-private partnerships is discussed not only in this strategy, but also as an important dimension of the current urban dynamics of large Brazilian cities